The house across the lake : a novel - Sager, Riley (Dutton, an imprint of Penguin Random House LLC, 2022)
"The new thriller from New York Times bestselling author Riley Sager in which a recently fired Broadway star flees to a remote Vermont lake house, only to find out that the area has a history of missing women"--